The Influence of Recommendation System Quality on E-commerce Customer Loyalty with Cognition Affective Behavior Theory (Journal of Advances in Information Systems and Technology, 2023)
The high number of internet users and the growth of e-commerce make it important for companies or businesses that provide e-commerce services to know the quality of their services to increase customer trust and loyalty. In addition, with the proliferation of e-commerce, there is more information related to available products, sometimes it also causes problems that users feel confused and frustrated to sort out information and make purchase decisions. In some e-commerce, there is already a recommendation system that makes it easier for users to make their choice. This study aims to find out what factors affect customer loyalty to Shopee e-commerce as well as test how much influence the quality of Shopee's e-commerce recommendation system have on customer loyalty with user trust as mediation variables. This research uses a quantitative approach using cognition affective behavior theory. Data collection in this study was carried out by distributing questionnaires through Google forms with purposive sampling techniques. A total of 356 respondents have participated in the study. The obtained data were analyzed with partial least squares – structural equation model (PLS-SEM). From the results of the analysis, seven hypotheses exist. All independent variables affect dependent variables. It was found that recommendation quality (RQ) can affect directly on the LO or indirectly through the trust mediation variable (TR).